Extrapolating from an Inquiry into Curricular Issues Concerning the Adoption of English as Medium of Instruction in a Japanese University Situation - Glenn Toh (Universidad de La Sabana, 2016)
Japanese universities have lately begun to teach academic content in Englishinstead of Japanese. In this article, I examine curricular and ideological issuesrelated to having English as a medium of instruction (EMI) at a Japanese universitybefore examining their links to larger cultural-political forces in Japan, includingneoconservative agendas. My discussion is framed within the settingof a Japanese higher education facing the challenges of: (1) low enrolments andinstitutional solvency; (2) curricular reform in keeping with the need for institutionalrenewal. Specifically, based on a critical narrative inquiry into a workplaceencounter involving two university courses, one in introductory psychologyand another in English for Academic Purposes (EAP), I will explore the ideologically-embedded nature of discourses affecting professional understandings oflanguage, meaning making and curriculum. I will also observe that the 'changes'resulting from the adoption of EMI are only superficial and that the role andstatus of English, in reality, remains circumscribed. doi:10.5294/laclil.2016.9.1.9